Sugar Cane Preparing Machine for Squeezing Juice Cane - ปรืองาม, พิมพ์พรรณ; เล็กรุ่งเรืองกิจ, นงลักษณ์; เทอดวงศ์วรกุล, อนุพันธ์ (Engineering and Technology Horizons, 2020)
The continuous feeding sugar cane polishing and peeling machine was developed from the previous polishing one which had low performance because the sugar cane stalk was damaged. The new model adds the feeding unit in front of the peeling unit and spring to suit the diameter of sugar cane stalk. The speeds of the feeding unit were conducted at 16 rpm, 24 rpm and 36 rpm in conjunction with three speeds of the blade mechanism at, 864 rpm, 1080 rpm and 1152 rpm respectively. This study can be concluded that the optimum rotational speeds of the feeding units and the blade mechanism are 16 rpm and 1080 rpm, respectively. These paramters resulted in the highest working capacity of 115.86 kg/h with the polishing capacity of 91.06% and the weight loss of 19.01%.